2022
DOI: 10.1080/07011784.2022.2044385
|View full text |Cite
|
Sign up to set email alerts
|

Flood frequency analysis at ungauged catchments with the GAM and MARS approaches in the Montreal region, Canada

Abstract: Flood frequency analysis at ungauged catchments with the GAM and MARS approaches in the Montreal region, Canada

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Ungauged catchments are distributed worldwide in dry and humid environments [88]. For example, the catchment of the Imjin is extended between North and South Korea, classified as one the most critical basins in Korea, and management of flood there is hard to do due to the limitation and sharing of hydrology data between North and South Korea [92]. In Russia, a large country in Asia, nearly 2.6 million streams are still recorded as ungauged or poorly observed data [93], and they developed a hydrology model Multi-Layer Conceptual Model, 3rd generation) (MLCM3) by the Russian State Hydrometeorological University.…”
Section: Ungauged Catchmentsmentioning
confidence: 99%
“…Ungauged catchments are distributed worldwide in dry and humid environments [88]. For example, the catchment of the Imjin is extended between North and South Korea, classified as one the most critical basins in Korea, and management of flood there is hard to do due to the limitation and sharing of hydrology data between North and South Korea [92]. In Russia, a large country in Asia, nearly 2.6 million streams are still recorded as ungauged or poorly observed data [93], and they developed a hydrology model Multi-Layer Conceptual Model, 3rd generation) (MLCM3) by the Russian State Hydrometeorological University.…”
Section: Ungauged Catchmentsmentioning
confidence: 99%
“…Several studies have used artificial intelligence‐based techniques to address regional flood frequency analysis issues (e.g. Alobaidi et al, 2015; Aziz et al, 2014, 2015, 2017; Dawson et al, 2006; Desai & Ouarda, 2021; Msilini et al, 2022; Ouarda & Shu, 2009 and Shu & Ouarda, 2007, 2008), and these studies have shown that nonlinear techniques usually outperform linear ones. GAMs have also recently been used in regional flood frequency analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological processes, including nonlinearity, are inherently complex in a variety of ways (Chebana et al, 2014; Desai & Ouarda, 2021; Msilini et al, 2022; Ouarda et al, 2018). In many cases, the linearity assumption in hydrology is violated; for example, larger catchments behave differently than smaller ones, and drier antecedent catchment states produce relatively less runoff for a given rainfall than wetter ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is problematic for our application as typical hydrologic data sets used in regional analyses contain a large number of candidate variables, many of which are highly correlated. For these reasons, current applications of GAMs to flood quantiles commonly rely on backwards stepwise selection (Chebana et al, 2014;Rahman et al, 2018;Noor et al, 2022;Msilini et al, 2022) sometimes coupled with a pre-selection step as in Dubos et al (2022). Backward selection approach used for GAMs has the potential to select appropriate covariates at the same rate as shrinkage approaches, but only when the information content of the data is high (Marra and Wood, 2011).…”
Section: Introductionmentioning
confidence: 99%